Acceptability and Feasibility of Reducing Unsafe Abortion through Medication among Early Pregnant Women who are Attending in RHSTEP at DMCH (Anwer Khan Modern Medical College Journal, 2017)
Background: Over the past two decades, the health evidence, technologies and human rights rationale for providing safe, comprehensive abortion care have evolved greatly. Unsafe abortion is one of the four main causes of maternal mortality and morbidity.Material & Methods: A prospective study were done from December, 2013 to January, 2015, over 13th months in RHSTEP at DMCH. Pregnant women of 5-9 weeks of pregnancy wanted to terminate their pregnancy were included in this study. Pregnant women had over 9th week of pregnancy, ectopic pregnancy, molar pregnancy and severe anemia were excluded from this study. A total 294 patients were enrolled in this study and MRM service was given them.Results: Among the 294 patients 268 (91%) found successful termination of pregnancy and 26 (8.8%) patients found unsuccessful termination. In these 26 patients, 24 had incomplete abortion and two had viable pregnancy (failed MRM). Most of the patients complained of moderate bleeding (156) and pain (182) after taking medication but some of them revealed excessive bleeding (138) and marked pain relieved by pain killer (112). Some of them also had fever (76), nausea (82), diarrhea (12), vertigo (30) and few also found itching palm (05) and oral ulcer (02). 87% patients told overall side effects were acceptable and 8 % said natural & only 5 % found unacceptable. On interview about the satisfaction of the patients in using this method for early termination, 90 % patients were satisfied with this method.Conclusion: Menstrual regulation with medication (MRM) using mifepristone and misoprostol is a safe, effective and acceptable method for early termination of pregnancy. Expansion of this service will reduce unsafe abortion in our country.Anwer Khan Modern Medical College Journal Vol. 7, No. 1: Jan 2016, P 23-27